2013
DOI: 10.1186/1471-2393-13-222
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatitis B in pregnant women and infants: a multicentre audit from four London hospitals

Abstract: BackgroundPregnant women with hepatitis B virus (HBV) infection can transmit the infection to their infants, screening of patients and appropriate interventions reduce vertical transmission. This audit was conducted to assess adherence to the national guidelines for management of HBV infection in pregnancy.MethodsA retrospective audit was conducted on pregnant women diagnosed with hepatitis B on screening in antenatal clinics, across four hospitals in London over 2 years (2009–2010). Data was collected from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…This included suboptimal rates of timely HBIg administration, assessment of maternal viral replication status, referral and engagement with specialist HBV care, completion of the infant HBV vaccine schedule and serological testing of the infant for CHB infection or immunity. According to International Guidelines, appropriate maternal HBV care includes referral to either an Infectious disease specialist or a Gastroenterologist/Hepatologist to assess the requirement for antiviral therapy, long‐term HBV and hepatocellular carcinoma (HCC) surveillance . The National Health Service in the UK recommends specialist review for all CHB mothers within 6 weeks of antenatal screening results .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This included suboptimal rates of timely HBIg administration, assessment of maternal viral replication status, referral and engagement with specialist HBV care, completion of the infant HBV vaccine schedule and serological testing of the infant for CHB infection or immunity. According to International Guidelines, appropriate maternal HBV care includes referral to either an Infectious disease specialist or a Gastroenterologist/Hepatologist to assess the requirement for antiviral therapy, long‐term HBV and hepatocellular carcinoma (HCC) surveillance . The National Health Service in the UK recommends specialist review for all CHB mothers within 6 weeks of antenatal screening results .…”
Section: Discussionmentioning
confidence: 99%
“…The National Health Service in the UK recommends specialist review for all CHB mothers within 6 weeks of antenatal screening results . A multicentre retrospective audit of four UK hospitals identified a 60% rate of specialist referral for mothers with CHB . A single US centre found that 19% of CHB mothers received appropriate HBV care post‐partum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, identification of HBsAg-positive mothers is not enough because the necessary measures are often not taken. Even in developed countries like the UK [60] or New Zealand [61] viremia is often not determined and an indicated antiviral therapy not initiated. If the current possibilities of diagnosis and therapy would be implemented, mother-to-child transmission of HBV could be prevented completely.…”
Section: Treatment Of Pregnant Women With High Viremiamentioning
confidence: 99%
“…Saudi Arabia).Infection with hepatitis B in newborns of carrier mothers is the leading cause of development of chronicity state up to 80% of the disease, Interrupting of HBV transmission through administration a highly effective neonatal immune-prophylaxis by vaccination and intra-venous immunoglobulin (IVIG) in the first 24 hours of life has a major impact in reducing the prevalence of cases. Despite immune-prophylaxis there are still documented cases of vertical transmission of HBV (5). In study conducted in china (2014), Vertical transmission rate has been reported around (5.44%) of infants despite immune-prophylaxis.…”
mentioning
confidence: 99%